An optimized SDS‐PAGE protocol with a new blotting system for the initial testing procedure of ESAs in doping control. Issue 1 (2nd December 2020) - Martin, Laurent; Martin, Jean‐Antoine; Audran, Michel; Marchand, Alexandre
Abstract: Recombinant erythropoietins (rEPOs) are still among the substances endurance athletes use for doping. Detection methods are based on an electrophoretic separation of the proteins followed by a western blot and immunodetection with specific anti‐EPO antibodies. In addition to IEF‐PAGE, the SDS‐PAGE method has been used to differentiate endogenous EPO from rEPOs by their molecular weight (MW). However, to adapt to new generations of rEPOs exhibiting higher MW, which were not well detected after SDS‐PAGE, sodium lauroyl sarcosinate (SAR) is now used instead of sodium dodecyl sulfate (SDS) for the initial EPO testing procedure on doping control samples. The SAR‐PAGE method is nevertheless expensive as it requires frequent buffer preparations using highly purified sarkosyl powder. In addition, this reagent needs to be handled with care due to acute toxicity by inhalation. The aim of this work was to improve the SDS‐PAGE method by increasing its sensitivity and transfer of high‐MW rEPOs. First, using a biotinylated primary anti‐EPO antibody and avoiding the use of a secondary antibody increased the general sensitivity of both SDS‐PAGE and SAR‐PAGE to all rEPOs about four‐fold. Then, by changing the buffer system during the protein transfer, with a CAPS buffer and a discontinuous buffer transfer system, high‐MW rEPOs, EPO‐Fc and CERA were transferred with higher efficiency and detected with high sensitivity. This optimized SDS‐PAGE protocol could be adopted by anti‐doping laboratories as an alternative to SAR‐PAGE.